Analysis of psychological experiences of Iranian elite athletes in home quarantine quaid-19: Phenomenological study 1 - Shahabi Kaseb, M. R.; Askari Tabar, E. S.; Ayobzade, K. (Sport Psychology Studies, 2020)
By spreading of Quaid-19 virus in Iran, most sports clubs were closed and league and championship matches were cancelled. The purpose of this study was to investigate the psychological experiences of Iranian elite athletes in quarantine due to the prevalence of coronavirus. Methodologically, this research is in the range of qualitative studies and a kind of phenomenological research. The population of the present study included Iranian elite male and female athletes (participation in premier leagues and membership in national teams) in various sports who had experience of living in home quarantine in the last 60 days. Participants in the study were selected in a purposeful sampling way and the sampling continued until to reach saturation. In general, 20 elite athletes were interviewed. A seven-step Colaizzi method was used to analyze qualitative data. Based on the analysis of the findings of the present study, nine main themes were achieved including problem-oriented coping strategies, task-oriented goal orientation, cognitive flexibility, compromised strategy of emotion cognitive regulation, negative self-assessment, negative mood, lack of enough motivation, cognitive anxiety, and feeling of homesickness. The results of the present study showed that home quarantine had different positive and negative psychological effects on Iranian elite athletes due to the prevalence of Quaid-19 disease. Awareness and mutual understanding of the psychological experiences of these athletes during the home quarantine period can provide the way for the necessary decisions during the corona and post-corona period by the country's sports managers and officials.